1970
DOI: 10.1136/bmj.2.5710.629
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Workers Exposed to Dusts Containing Derivatives of Bacillus Subtilis

Abstract: Gastrin Secretion in Peptic Ulceration-Byrnes et al. MEDIBARmJoUwL 629 responsive to changes in blood glucose, and evidence has been provided that this action is probably mediated by the hypothalamus, constituting a physiological "feedback" mechanism. We thank the physicians and surgeons of St. Vincent's Hospital for referring patients under their care to this study, and Mr. F. B. Griffiths and Miss S. Whitington for performing blood glucose estimations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Subtilisin Carlsberg (Alcalase), a class A subtilase produced by Bacillus licheniformis, is one of several subtilases used in detergent formulations. Soon after the initiation of large-scale production of enzyme-containing detergents, allergic respiratory reactions to the enzyme components were noted among factory workers (44,45). Thus, Tri r 2 is a member of the same enzyme family as an antigen previously related to asthma.…”
Section: Demonstration Of the Immune Response To Tri R 2-mentioning
confidence: 99%
“…Subtilisin Carlsberg (Alcalase), a class A subtilase produced by Bacillus licheniformis, is one of several subtilases used in detergent formulations. Soon after the initiation of large-scale production of enzyme-containing detergents, allergic respiratory reactions to the enzyme components were noted among factory workers (44,45). Thus, Tri r 2 is a member of the same enzyme family as an antigen previously related to asthma.…”
Section: Demonstration Of the Immune Response To Tri R 2-mentioning
confidence: 99%
“…Workers involved in preparing enzyme mixes or adding enzyme to detergent base have the highest risk of sensitization with subsequent development of respiratory disease [26]. Atopy has been re ported by some investigators to predispose individuals to sensitization [11,26] while others report no difference in the frequency of sensitiza tion between atopic and nonatopic workers [25]. This apparent discrep ancy can in part be reconciled by the observation that atopic individuals may become skin test positive more quickly than nonatopic persons, but nonatopic individuals will respond to skin testing following continued exposure [12].…”
Section: Introductionmentioning
confidence: 99%
“…The investigators repeated the same tests 6 months later and found that negative enzyme sensitivity could turn positive, despite the breaking of its relationship with Bacillus subtilis enzymes. The derangement in the pulmonary function tests could be severe and irreversible [13].…”
Section: Discussionmentioning
confidence: 99%